Amorphous nanophotonics - Scharf, Toralf; Rockstuhl, Carsten (Nano-Optics and Nanophotonics, 2013)
This book represents the first comprehensive overview over amorphous nano-optical and nano-photonic systems. Nanophotonics is a burgeoning branch of optics that enables many applications by steering the mould of light on length scales smaller than the wavelength with devoted nanostructures. Amorphous nanophotonics exploits self-organization mechanisms based on bottom-up approaches to fabricate nanooptical systems. The resulting structures presented in the book are characterized by a deterministic unit cell with tailored geometries; but their spatial arrangement is not controlled. Instead of periodic, the structures appear either amorphous or random. The aim of this book is to discuss all aspects related to observable effects in amorphous nanophotonic material and aspects related to their design, fabrication, characterization and integration into applications. The book has an interdisciplinary nature with contributions from scientists in physics, chemistry and materials sciences and sheds light on the topic from many directions.